ANALISIS PENGARUH PENJUALAN, BIAYA PRODUKSI, DAN BIAYA OPERASIONAL TERHADAP LABA PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Pramudyanti, Naomi; Nurdiwaty, Diah; Linawati, Linawati (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Manufacturing companies, especially the food and beverage subsector, play an important role in national economic growth. This study aims to analyze the effect of sales volume, production costs, marketing costs, and administrative and general costs on the net profit of food and beverage companies listed on the Indonesia Stock Exchange for the period 2022–2024. Using a quantitative approach with multiple linear regression methods, this study involved 27 companies selected through purposive sampling techniques, resulting in 81 observation data over three years. Data were obtained from the company's annual financial reports through the website [www.idx.co.id](http://www.idx.co.id) and processed using SPSS version 25. The results of the study show that partially, production costs, marketing costs, and administrative and general costs have a significant effect on net profit, while sales volume does not have a significant effect. Simultaneously, these four variables have a significant effect on net profit. This finding confirms that cost management efficiency plays a greater role in increasing net profit than increasing sales volume.